Comparison of different treatment methods for protein solubilisation from waste activated sludge. (1st October 2017) - Xiao, Keke; Chen, Yun; Jiang, Xie; Seow, Wan Yi; He, Chao; Yin, Yao; Zhou, Yan
Abstract: Biomaterials recovery from wasted activated sludge has become an increasing interesting research topic. The purpose of this study was to systemically evaluate different sludge disintegration methods (ultrasonic, alkaline, and thermal treatments) for protein solubilisation from waste activated sludge (WAS). Compared to control without treatment, the soluble protein concentration increased by 11, 23 and 12 times under the optimal treatment conditions (ultrasonic treatment of 1 W mL −1, alkaline treatment of pH 12 and thermal treatment at 80 °C). The increased soluble protein were significantly correlated with the release of total organic carbon (TOC), total dissolved nitrogen (TDN) and total organic nitrogen (TON) in soluble EPS, and the degradation of above parameters in tightly bound EPS. For all sludge samples treated by various methods, tyrosine-like protein with molecular weight less than 20 kDa predominated, and alkaline treatment at pH 12 showed the highest protein dominance. Further surface analysis of sludge by X-ray photoelectron spectroscopy indicated this might be related with the significant protein-N conversion occurred at pH 12. The economic analysis indicated alkaline treatment at pH 12 was economically feasible with a net saving of 25.57 USD per ton wet sludge compared to conventional sludge treatment and disposal method. Graphical abstract: Highlights: Protein solubilisation was negatively correlated to TOC, TDN and TON in TB EPS. Molecular weight of soluble protein was mainly less than 20 kDa for all samples. X-ray photoelectron spectroscopy was used to investigate N transformation in solid. The feasibility of method for protein recovery was assessed with economic analysis.